Incidence and mortality of pancreatic cancer on a rapid rise in Taiwan, 1999–2012. (August 2017) - Tseng, Chao-Ming; Huang, Shih-Pei; Liao, Wei-Chih; Chiang, Chun-Ju; Yang, Ya-Wen; Chang, Chi-Yang; Hsu, Yao-Chun; Chen, Hui-Chi; Chiang, Han-Sun; Lin, Jaw-Town
Highlights: This study analyzed national database to evaluate the trend of pancreatic cancer in Taiwan. Both the incidence and mortality have been significantly rising from 1999 to 2012. The incidence and mortality were projected to increase by 20% in the next decade. Abstract: Background: Accumulating data has revealed a rapidly rising incidence of pancreatic cancer in Western countries, but convincing evidence from the East remains sparse. We aimed to quantify how the incidence and mortality rates of pancreatic malignancy changed over time in Taiwan, and to develop future projection for the next decade. Methods: This nationwide population-based study analyzed the Taiwan National Cancer Registry and the National Cause of Death Registry to calculate the annual incidence and mortality rates of pancreatic malignancy from 1999 to 2012 in this country. The secular trend of the incidence was also examined by data from the National Health Insurance Research Database. Results: A total of 21, 986 incident cases of pancreatic cancer and 20, 720 related deaths occurred during the study period. The age-standardized incidence rate increased from 3.7 per 100, 000 in 1999 to 5.0 per 100, 000 in 2012, with a significant rising trend (P < 0.01). The increase was nationwide, consistently across subgroups stratified by age, gender, geographic region, and urbanization. Data from the National Health Insurance Research Database corroborated the rise of incident pancreatic cancer. Mortality also increased with time, with the age-standardized rate rising from 3.5 per 100, 000 in 1999 to 4.1 per 100, 000 in 2012 (P < 0.01). In accordance with the incidence, the mortality trend was consistent in all subgroups. Both the incidence and mortality were projected to further increase by approximately 20% from 2012 to 2027. Conclusion: The incidence and mortality of pancreatic cancer have been rapidly rising and presumably will continue to rise in Taiwan.